"Who would want to lay down into the permafrost?": an attempt to explain differences in migration rates, strategies and attitudes in two Russian northern cities. (3rd July 2021) - Istomin, Kirill V.
ABSTRACT: The macro-level explanations for the massive outflux of the population from the Russian Arctic after 1991 mostly do not account for local differences in out-migration rates. At the same time, these differences can be exceptionally large. This paper uses ethnographic methods to explain significant differences in the rates of population outflux between the cities of Vorkuta and Ukhta, Komi Republic, Russia, which exist despite the very similar history and current social and macroeconomic situation of the two cities. The study indicates differences in attitudes to migration and in-migration strategies among the inhabitants of the two cities. It is suggested that the presence of a large group of inhabitants with the same geographic origin and the same solidarity-promoting occupation in Vorkuta, but not in Ukhta, in the late Soviet period can partly explain this difference. The migration of the members of this group back towards the region of their origin created a migration network with certain cultural norms and expectations related to it; thus, a certain culture of migration emerged. The study points to the potentially significant role of social and cultural factors in shaping the patterns of recent migrations from the Russian Arctic.